From K-pop to C-pop: Feasibility Exploration of Building a Chinese Star-Making System Based on the Korean Local Idol Model - Li, Zhuoxin; Sun, Yutong; Zhan, Yufan (Transactions on Social Science, Education and Humanities Research, 2024)
In today’s increasingly globalized world, where the economy is rapidly advancing, a cultural phenomenon known as K-pop has been gradually gaining prominence. Originating from South Korea, K-pop has not only made a significant impact on neighboring countries within Asia but has also captivated audiences in the Western world. This cultural wave has effectively positioned South Korea as the epicenter of the emerging East Asian trend culture. However, China, with its rich cultural heritage, has faced obstacles in cultivating its own idol industry. While C-pop, the Chinese pop music genre, has struggled to establish a significant presence both in terms of scale and quality, it is important to recognize the immense market potential and promising future of the Chinese idol industry. This paper focuses on idol groups associated with the famous Korean entertainment company JYP. It aims to meticulously examine the key factors that have contributed to the development and prosperity of K-pop. By doing so, it seeks to analyze the characteristic path suitable for the development of China’s idol industry.